Efektivtas Biaya Medis Langsung Penggunaan Antibiotik Golongan Sefalosporin Generasi Ketiga Pada Pasien Tifoid Di Rumah Sakit Rawa Lumbu - Mayolla Amanda; Maratun Shoaliha (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Typhoid fever is an acute infection caused by the bacterium Salmonella enterica reservoir typhi, commonly called Salmonella typhi (S.typhi). The purpose of this study was to determine the effectiveness of direct medical costs using third-generation cephalosporin class antibiotics, namely ceftraixone, cefotaxime, cefixime in typhoid fever patients at Rawa Lumbu Bekasi Hospital. This study used a retrospective method. The number of samples is 100 patients. Data analysis was performed using a frequency distribution. Results The results showed that most of the respondents were male (57%). Based on age, the highest number is in the age range of 36-45 years (42%). Based on length of stay, the highest number was 1-5 days (65%). The most widely used antibiotic was ceftriaxone (61%). The highest average cost was the use of cefixime (Rp. 3,327,761) and the lowest average cost was the use of ceftriaxone (Rp. 2,973,568). The average direct medical costs used in the treatment of typhoid fever using ceftriaxone therapy is IDR 2,973,568. For cefotaxime therapy it was Rp. 3,200,218 while for cefixime therapy it was Rp. 3,306,262.